AGRO ECOLOGICAL CONDITIONS AND DEVELOPMENT POSSIBILITIES OF SUSTAINABLE AGRICULTURE - Bošković, Jelena; Simić, Jeremija; Hojka, Zdravko; Vukosav, Marija; Sarić, Mirko (Economics of Agriculture, 2006)
The World Commission on Environment and Development called attention to the basic changes in human population growth, need for strategies for attaining security in food production and need for conversation of natural resources. Sustainable agriculture goals may be shortly abridged to stable market supply by biologically quality food, on employment of rural population and suppressing of poverty, as well as the management of natural resources and environment protection on local and global level. For the system of such sustainable and organic agriculture, ecology provides basic conditions through the development of diversified agro ecological systems. Integration of plant and animal biodiversity, which improves complex of interaction and synergy, is the advantage. This enables biological regulation of harmful organisms, nutrition circling, biomass production and accumulation. The result of the agro ecological planning is improvement of economical and ecological agro ecology system maintenance. Strategy of sustainable agriculture development is basically based on improvement of conservation and increase of local agricultural resources. Within this, the greatest efforts are necessary for harmonization of environment laws with needs of macro economic policy on national and international levels. In accomplishing of these aims are included new initiatives in education, application of economical stimulations and development of relevant new technologies.